Umbrella‐Popcorn Chip With Planar Hotspots Enables Uniform SERS Fingerprinting for Accurate HPV DNA Subtyping and Clinical Validation - Liangliang Jiang; Zibo Gao; Xianqi Sun; Chaochao Ma; Guangrun Wu; Siqi Gong; Jiacheng Li; Yaowen Xing; Mingxu Zhang; Yingji Wang; Jing Wu; Jing Wang; et al. (Advanced Functional Materials, 2026)
ABSTRACT Conventional SERS‐based nucleic acid typing is severely challenged due to the dominance of adenine signals, obscuring the accurate detection of other nucleobases and thus limiting precise DNA fingerprinting. Herein, we introduce U‐PopChip (Umbrella‐Popcorn Chip), a novel SERS substrate engineered with uniformly distributed surface hotspots through umbrella‐shaped structured templates integrated with silver “popcorn” nanoparticles. Calculate the angle between complementary bases and the substrate surface, confirming that all four bases are nearly perpendicular to the substrate surface. Quantitatively demonstrate that this perpendicular orientation effectively eliminates angle‐induced enhancement bias. This innovative design significantly mitigates the overwhelming A‐base signals, enabling balanced and ultrasensitive detection of all four nucleobases (A, T, C, G). Coupled with machine learning algorithms, the platform demonstrated precise subtype discrimination of high‐risk HPV DNA, HPV 18 DNA the lowest detection concentration achieving 19.2 copies/mL. Validation in clinical cervical secretion samples exhibited excellent consistency with conventional Gene chips and TCT results. This study provides a transformative approach, significantly enhancing the practical capability of SERS technology for viral nucleic acid typing and clinical diagnostics.